KARANGTARUNA EMPOWERMENT THROUGH PUBLIC SPEAKING TRAINING FOR LEGAL COUNSELING AND K3LH MOBILIZATION: POST-EARTHQUAKE SOLUTIONS - Retnowati, Nanik; Anggrayni, Dewi; Fajri, Ibrahim (LPPM Univ. Ibn Khaldun Bogor, 2023)
The earthquake has devastated various sectors in the affected area. Kampong Pakalongan, Padaluyu Village, Cugenang, Cianjur District is one of the affected areas. Karang Taruna is one of the important elements of society that must be empowered to move society to rise. They can be empowered more with good communication skills. Through a community service incentive program funded by the Directorate General of Higher Education, public communication training was conducted, the program initiated was empowering Karang Taruna with public speaking skill to help managing lost documents and mobilizing residents to carry out Environmental Occupational Health and Safety (K3LH). The program involved thirty members of Karang Taruna in public communication training activities. The goal of this training is to help youth organizations help people who have lost documents and mobilize residents to carry out K3LH, working together to clean up building debris. The training is carried out directly in the field using lecture and discussion methods. The participants could also access infographics broadcasted at YouTube channel https://youtu.be/E3SDsTzabZM. This program can facilitate UIKA to complete IKU 2, 3, and 4, which benefits lecturers, students, and the community all at once.